Chronic fatigue and immune deficiency syndrome (CFIDS), cellular metabolism, and ionizing radiation: a review of contemporary scientific literature and suggested directions for future research. (4th March 2018) - Rusin, Andrej; Seymour, Colin; Mothersill, Carmel
Abstract: Purpose: To investigate biochemical pathways known to be involved in radiation response and in CFIDS to determine if there might be common underlying mechanisms leading to symptoms experienced by those accidentally or deliberately exposed to radiation and those suffering from CFIDS. If such a link was established to suggest testable hypotheses to investigate the mechanisms with the aim of identifying new therapeutic targets. Conclusions: Evidence for involvement of the alpha-synuclein, cytochrome c oxidase, αB-crystallin, RNase L, and lactate dehydrogenase/STAT1 pathways is strong and suggests a common underlying mechanism involving mitochondrial dysfunction mediated by ROS and disruption of ATP production. The downstream effect of this is compromised energy production. Testable hypotheses are suggested to investigate the involvement of these pathways further.